Atributos do solo e dendrometria em agrofloresta no Sudoeste do Paraná - Dalposso, David Marlon (2017)
The study of the variability of the chemical, physical and biological attributes of the soil is of paramount importance to execute the correct management of the soil, as well as the use of technological tools in order to facilitate and intensify the knowledge of the relationships and soil-plant correlations. After the general introduction the study addressed the soil variables of agricultural and silvicultural interest in the form of a scientific article of number one, in order to provide the knowledge of different land use and management systems compared to agroforestry, evidencing that there is a relation of Cause and effect among these study environments, revealing their variability. In the second article the geostatistical question was addressed, which makes it possible to make a more detailed and localized study of the different chemical, physical and biological aspects of the soil, generating thematic maps of the behavior of each variable in question. Finally, the last chapter dealt with the correlation of soil attributes with dendrometric variables of the agroforestry, in order to understand the relationship between them, whether positive or negative, high or low, thus inferring the success of the crop for a given soil condition , handling, system of use. For the first article, the systems presented variability among the chemical, physical and biological attributes of the soil, where the highest organic matter contents prevailed in the native forest, followed by lower density and higher soil moisture. The integration-crop-livestock showed the highest resistance to soil penetration and the lowest content of organic matter, even the highest soil density. The highest macroporosity and total porosity were observed in the native forest for a depth of 10-20 cm. The highest number of insects was observed in the Crop-Livestock Integration, but less diversity and richness and greater dominance. In the second article, spatial variability was verified for the chemical, physical and biological attributes of the soil, presenting different ranges and spatial dependencies through the semivariograms of kriging. Finally, the third article presented a correlation only between the chemical saturation of soil bases and basal area in the 0-5 cm layer of the soil, being this high and inverse, as well as for resistance to soil penetration at the depth of 20- 50 cm. It should be noted that there is variability of soil attributes in different management and use systems, as well as spatial variability for soil attributes. Also, there is correlation of some soil chemical and physical attributes with dendrometric variables of agroforestry production.